Analysis of the efficiency of public policies in municipalities, with a population of over 10.000 habitants in the administrative region of Presidente Prudente - Data from COVID-19 - Martins, Prof. Dr. Moises da Silva (International Journal of Advanced Engineering, Management and Science, 2021)
Pandemics, such as that of COVID-19, affect a large number of people, imposing new rules and social habits on them, aiming to modify the behavior that influences economic and social problems. In this context, the objective of this study was to be investigative, using the DEA tool (data envelopment analysis), seeking the efficiency of proposed and economic measures, seeking to assist them and also public policies in improving planning, trying to avoid problems such as those caused by the current pandemic. This is a cross-sectional and quantitative study, of an exploratory nature, carried out with data from the 10th. Region of the state of São Paulo, based on municipalities with 10,000, or more, inhabitants in the time interval from 05/03/2020 to 05/05/2021. This work is justified by the fact that the COVID-19 pandemic exposes structural weaknesses, economic differences and bottlenecks in the Brazilian health system, especially the lack or uneven distribution, in the territory, of health professionals and health professional, infrastructure, as well as limited production capacity, poor income distribution, the human development index and, still, the glaring differences in the GDP of the municipalities. It has been noted that 53% of the municipalities are deficient and that only 47% of them are above the average ideal efficiency rate of 0.823150. It is concluded, in this work, that the economic and social factors need to be better addressed and that social distance, the use of masks and personal hygiene must be encouraged by the representatives of the public power, in order to avoid a greater number of deaths.